EFEK TEMPERATUR TERHADAPVIRULENSI JAMUR Colletotrichum gloeosporioidesPenz. Sacc.PENYEBAB PENYAKIT ANTRAKNOSA PADATANAMAN KAKAO(Theobroma cacao L.) - Tatik Fadilah Hakim Harahap1; Lahmuddin Lubis; Hasanuddin Hasanuddin (Universitas Sumatera Utara, 2013)
Temperature Effect TowardsVirulency ofColletotrichum gloeosporioides Penz. Sacc. FungalDisesase Caused of Anthracnose on Cocoa(Theobroma cacaoL.).This research aims to determindvirulency level, disease incident and temperature effect towards fungal morphology growth of C.gloeosporioides fungal disesase caused of anthracnose oncocoa (Theobroma cacao L.). The studywas conductedat Karang Anyar village, regency in Langkat with altitude±28masl, at Sambirejovillage, regency in Langkat with altitude±28masl, at Bekukul village, regency in Deli Serdang withaltitude±100 masl, at Sayum Sabah village, regency in Deli Serdang with altitude±200 masl and atthe Laboratory ofPlant Disease, Agroecotechnology Program Study, Faculty of AgricultureUniversity of Sumatera Utara, Medan from July to December 2012.The method of this research issurvey.Results showedthat highest attack percentage was founded in Sambirejo villagewhich reach100% and thelowest was founded in Sayum Sabah village which reach 95%, highest diseaseseverity was founded in Bekukul village which reach 92.0% and thelowest was founded in KarangAnyar village which reach 78.6% and showed no differences fungus morphology that extractedfrom four different location.Keywords: C. gloeosporioides,virulency, morphology, temperature, cocoa